The Accommodation Potential of Implicative Verbs - van Leusen, Noor (Proceedings of the Amsterdam Colloquium, 2011)
We present an analysis of implicative verbs,1 complement-taking verbs which induce entailment-like inferences, but which are also claimed to trigger presuppositions. What is presupposed, however, is much more variable than with e.g. factive verbs. Sketching a formal treatment in Logical Description Grammar we consider the role of pragmatic reasoning and accommodation in deriving these presuppositions.